Digital Literacy and Business Networks on Business Competitiveness For Business Sustainability - Wawan Ruswandi; Rosanna Wulandari; Asep Deni; Eris Juliansyah; Ce Mulya Rizki Anugrah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The Ministry of Cooperatives and SMEs implements policies to increase the productivity and competitiveness of SMEs at the international level. In order for SMEs to be more competitive, there needs to be business management education from the government, academics, and the community. This will provide advantages and support business sustainability. Business actors also need to master digital literacy and collaborate with business networks. This research aims to identify how digital literacy and business networks can improve MSME competitiveness and sustainability. An explanatory approach is used to understand business sustainability, competitiveness, digital literacy, and business networks, while a conclusive approach analyzes the hypothesis. Path analysis was performed using SPSS26. Samples were taken using probability sampling and the Slovin formula with a 10% margin of error, consisting of business actors in Sukabumi Regency. The results are: 1.Digital literacy has a tremendous impact on business competitiveness. 2.Business networks contribute tremendously to business competitiveness. 3.Digital literacy contributes tremendously to business sustainability. 4.Business networks contribute tremendously to business sustainability. 5.Business competitiveness contributes tremendously to business sustainability. 6.Digital literacy contributes tremendously to business sustainability through business competitiveness and 7. Business networks contribute tremendously to business sustainability through business performance.